Risk heterogeneity and credit supply: Evidence from the mortgage market - Timothy Besley; Neil Meads; Paolo Surico (Bank of England, External Monetary Policy Committee Unit, 2010)
This paper uses a unique data set on more than 600,000 mortgage contracts to estimate a credit supply function which allows for risk-heterogeneity. Non-linearity is modelled using quantile regressions. We propose an instrumental variable approach in which changes in the tax treatment of housing transactions are used as an instrument for loan demand. The results are suggestive of considerable risk heterogeneity with riskier borrowers penalised more for borrowing more.
Keywords: D10; E21; G21; 330; mortgage individual data; credit supply; risk pricing; heterogeneous effects; instrumental variable; Immobilienmarkt; Hypothek; Kreditgeschäft; Risikopräferenz; Grundsteuer; Steuerreform; Nachfrage; Großbritannien